2005
DOI: 10.1021/jp050625p
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Sensing of DNA Hybridization on Conducting Polymer Film-Modified Diamond

Abstract: The impedimetric sensing of DNA hybridization on polyaniline/polyacrylate (PANI/PAA)-modified boron-doped diamond (BDD) electrode has been investigated. An ultrathin film of PANI-PAA copolymer was electropolymerized onto the diamond surfaces to provide carboxylic groups for tethering to DNA sensing probes. The electrochemical impedance and the intrinsic electroactivity of the polymer-diamond interface were analyzed after the hybridization reaction with target and non-target DNA. The impedance measurement shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
3
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 30 publications
(54 reference statements)
3
110
3
4
Order By: Relevance
“…The field-effect in NCD substrates, caused by negatively charged DNA at the surface, has been reported in our previous work on real-time impedimetric DNA detection [10] as well as in other publications [9,28] and will not be discussed here. A negligible field-effect in the NCD substrate was observed during CRP treatment, reflected by the lack of impedance variations in the semi-circle.…”
Section: High Frequency Rangementioning
confidence: 81%
“…The field-effect in NCD substrates, caused by negatively charged DNA at the surface, has been reported in our previous work on real-time impedimetric DNA detection [10] as well as in other publications [9,28] and will not be discussed here. A negligible field-effect in the NCD substrate was observed during CRP treatment, reflected by the lack of impedance variations in the semi-circle.…”
Section: High Frequency Rangementioning
confidence: 81%
“…The overall performance of the diamond nano-wire DNA sensor in comparison to published data available in the literature for Au, [43][44][45][46] and polycrystalline diamond, [47] using comparable DNA mere structures are shown in Fig. 5e [47]). Sensing by diamond nano-wires is about 100 to 1000 better than using smooth surfaces from Au and diamond.…”
Section: Resultsmentioning
confidence: 97%
“…Cai et al (2004) immobilized ssDNA onto Si electrodes, and demonstrated that they were able to distinguish complementary DNA from DNA containing 4-base mismatches as compared to the immobilized probe DNA (Cai et al, 2004). Gu et al (2005) and Vermeeren et al (2007) even succeeded in single-nucleotide polymorphism (SNP) sensitivity, the latter in real-time (Gu et al, 2005), (Vermeeren et al, 2007). Fig.…”
Section: Clinical Diagnosticsmentioning
confidence: 98%
“…Adapted from (Nebel et al, 2007). Gu et al (2005) functionalized p-type diamond with a PANI/polyacrylic acid (PAA) composite polymer films using CV. The p-type diamond working electrode was treated with the aniline and PAA monomeric solution, and by potential cycling the monomers were polymerized onto the electrode.…”
Section: Electrochemical Functionalizationmentioning
confidence: 99%